Checklist of Marine Fungi and Yeasts Associated with Holothuria (Mertensiothuria) leucospilota from Pangkor Island - Kamarudin, Kamarul Rahim; Mohamed Rehan, Maryam; Mohamed Rehan, Aisyah; Che Zahri, Mohd Zulhafiz; Muhd Lutfi, Fatin Najihah (Journal of Sustainable Natural Resources, 2020)
Marine microorganisms such as fungi and yeasts can adapt to extreme marine environment conditions and play different roles especially in the nutrient cycling and as bioindicator of ocean change. This study was carried out to isolate and identify fungi and yeasts associated with Holothuria (Mertensiothuria) leucospilota from Pangkor Island, Perak, Malaysia. Two specimens of H. leucospilota were collected from Giam Island and Teluk Nipah Beach of Pangkor Island. Nine samples of fungi and ten samples of yeasts were isolated from the internal and external parts of the H. leucospilota specimens such as cuticle, tentacle, coelomic fluid, cloaca, cuvierian tubules, and surrounding sediment and seawater. Polymerase Chain Reaction (PCR) and DNA sequencing of the Internal Transcribed Spacer (ITS) region were applied for species identification of the microorganisms. Sequence analyses of the ITS region resulted in the identification of five genera of fungi i.e. Cladosporium, Curvularia, Polyporaceae, Acremonium, and Penicillium; and four genera of yeasts i.e. Sterigmatomyces, Pichia, Debaryomyces, and Candida with some of them could be identified up to the species level. The fungi and yeasts isolated from the H. leucospilota specimens from Pangkor Island could have potential biotechnological applications which can be further characterised.